Advancements in Electrocatalytic Nitrogen Reduction: A Comprehensive Review of Single‐Atom Catalysts for Sustainable Ammonia Synthesis - Long, Xianhu; Huang, Fan; Yao, Zhangnan; Li, Ping; Zhong, Tao; Zhao, Huinan; Tian, Shuanghong; Shu, Dong; He, Chun (Small (Weinheim an der Bergstrasse, Germany), 2024)
Electrocatalytic nitrogen reduction technology seamlessly aligns with the principles of environmentally friendly chemical production. In this paper, a comprehensive review of recent advancements in electrocatalytic NH3 synthesis utilizing single‐atom catalysts (SACs) is offered. Into the research and applications of three categories of SACs: noble metals (Ru, Au, Rh, Ag), transition metals (Fe, Mo, Cr, Co, Sn, Y, Nb), and nonmetallic catalysts (B) in the context of electrocatalytic ammonia synthesis is delved. In‐depth insights into the material preparation methods, single‐atom coordination patterns, and the characteristics of the nitrogen reduction reaction (NRR) are provided. The systematic comparison of the nitrogen reduction capabilities of various SAC types offers a comprehensive research framework for their integration into electrocatalytic NRR. Additionally, the challenges, potential solutions, and future prospects of incorporating SACs into electrocatalytic nitrogen reduction endeavors are discussed. Electrocatalytic nitrogen reduction (NRR) technology harmonizes seamlessly with the principles of environmentally friendly production. Here, a comprehensive review of recent advancements in electrocatalytic NRR utilizing single‐atom catalysts (SACs) is presented. The systematic comparison of the NRR of various SAC provides a comprehensive research framework. Additionally, the challenges and future prospects of incorporating SACs into electrocatalytic nitrogen reduction endeavors are addressed.